Mutations in Nop60B, the Drosophila homolog of human Dyskeratosis congenita 1, affect the maintenance of the germ-line stem cell lineage during spermatogenesis. - Kauffman, T.; Tran, J.; Dinardo, S. (Developmental Biology, 2003)
Spermatogenesis in Drosophila is maintained by germ-line stem cells. These cells undergo self-renewing divisions and also generate daughter gonial cells, whose function is to amplify the germ cell pool. Gonial cells subsequently differentiate into spermatocytes that undergo meiosis and generate haploid gametes. To elucidate the circuitry that controls progression through spermatogenic stem cell lineages, we are identifying mutations that lead to either excess germ cells or germ cell loss. From a collection of male sterile mutants, we identified P-element-induced hypomorphic alleles of nop60B, a gene encoding a pseudouridine synthase. Although null mutations are lethal, our P element-induced alleles generate viable, but sterile flies, exhibiting severe testicular atrophy. Sterility is reversed by P-element excision, and the atrophy is rescued by a Nop60B transgene, confirming identity of the gene. Using cell-type-specific markers, we find that testicular atrophy is due to severe loss of germ cells, including stem cells, but much milder effects on the somatic cells, which are themselves maintained by a stem cell lineage. We show that Nop60B activity is required intrinsically for the maintenance of germ-line stem cells. The relationship of these phenotypes to the human syndrome Dyskeratosis congenita, caused by mutations in a Nop60B homolog, is discussed.